2023
DOI: 10.1039/d2nj05478g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bubble-templated electrodeposition of superhydrophobic Zn–Ni films

Abstract: When the water droplets contact an unclean superhydrophobic surface, they roll on the surface to take away the dust. Herein, self-cleaning superhydrophobic Zn-Ni films were fabricated using a dynamic hydrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…15a3). 24 Zhang et al obtained a superhydrophobic cauliflower-like structured Zn–Ni coating via a dynamic hydrogen bubble as the template, 167 and the influence of bath temperature on the surface topography was investigated. Shen et al also fabricated a Ni coating with flower-like structures and the gaps of ∼20 μm by magnetic-field-induced selective scanning electrodeposition based on additive manufacturing and adjusting the magnetic-field strength.…”
Section: Various Hierarchical Structures Of Superhydrophobic Surfaces...mentioning
confidence: 99%
See 1 more Smart Citation
“…15a3). 24 Zhang et al obtained a superhydrophobic cauliflower-like structured Zn–Ni coating via a dynamic hydrogen bubble as the template, 167 and the influence of bath temperature on the surface topography was investigated. Shen et al also fabricated a Ni coating with flower-like structures and the gaps of ∼20 μm by magnetic-field-induced selective scanning electrodeposition based on additive manufacturing and adjusting the magnetic-field strength.…”
Section: Various Hierarchical Structures Of Superhydrophobic Surfaces...mentioning
confidence: 99%
“…Electrodeposition is a process in which metal, alloys, and metal compounds are deposited on the conductive electrode surface from aqueous, non-aqueous, or dissolved salt of their compounds under the action of an electric eld. 167 Hierarchical structures can be obtained by controlling the electrodeposition parameters including solution concentration as well as the electrodeposition current and time. 202 It has been reported that certain one-step electrodeposited hierarchically structured coatings achieved This journal is © The Royal Society of Chemistry 2024 superhydrophobicity by organic adsorption in air for a certain amount of time, without chemical modication or adding a lowenergy material in the electrodeposition solution.…”
Section: Electrodepositionmentioning
confidence: 99%
“…Moreover, hydrogen-oxygen fuel cell design is focused on the production of electricity based on the O 2 reduction (to H 2 O) at the cathode, associated with the oxidation of H 2 at the anode [2][3][4], the catalytic four-electron (4e − ) or two-electron (2e − ) reduction of O 2 to water or H 2 O 2 [5][6][7][8]. Therefore, researchers focus their interests on the development of e cient and robust catalysts for O 2 reduction [9][10][11]. In Nature, cytochrome c oxidase (CcO) can e ciently catalyze the reduction of O 2 to H 2 O under mild conditions [12], but the stability is often limited outside of their native environment, because this reduction reaction takes place without releasing toxic partially reduced oxygen species [13,14].…”
Section: Introductionmentioning
confidence: 99%